Experience of Covid-19 Survivors in Relieving Symptoms of Anosmia - Amelia Diah Agustin; Sri Mugianti; Wiwin Martiningsih (Journal of Ners and Midwifery, 2023)
The high stigma of the community and public compliance in implementing health protocols can hamper the reduction of COVID-19 cases. One of the symptoms of COVID-19 is anosmia. The purpose of this study was to find out the experiences of survivors of Covid-19 to relieve symptoms of anosmia. The data collection method in this case study is through in-depth interviews. Data collection was carried out on January 10 2022-February 10 2022. The research design used a qualitative case study with 9 participants from Sumberjo Village who experienced symptoms of anosmia during COVID-19. Data collection tools use mobile phones and stationery. The sampling technique used is snowball. The results showed that all participants tried to eliminate the symptoms of anosmia. Four themes were found regarding the experiences of Covid-19 survivors in relieving anosmia symptoms, theme 1) efforts made to relieve anosmia symptoms were PHBS, use of pharmacological and nonpharmacological drugs, and olfactory training. Theme 2) the feelings felt when confirmed are still enthusiastic, afraid, anxious, and worried. Theme 3) Environmental responses to confirmed COVID-19 patients, including positive responses, are support systems in the family and environment, and negative responses are social stigma. Theme 4) symptoms of anosmia if confirmed with COVID-19 are respiratory tract disorders, muscle stiffness, thermoregulation, sleep disturbance, and fatigue. To relieve the symptoms of mia in the form of nasal irrigation with 0.9% NaCl solution, it is necessary to carry out tests at a later date, even though there are already researchers in several hospitals